Hedonic thresholds for sodium chloride reduction in cracker (Research, Society and Development, 2020)
One of the main factors responsible for the worldwide high hypertension rate is the excessive sodium intake. Currently, the population salt consumption is twice the recommended limit and thus initiatives to reduce this component content in food, especially industrialized products, have been targeted. In this context, this study aimed to investigate what amount of sodium chloride can be reduced from salted crackers without compromising its acceptance (compromised acceptance threshold - CAT) neither causing its sensory rejection (hedonic rejection threshold - HRT). The Hedonic Thresholds Methodology (HTM) was applied to determine the CAT and HRT, where the standard stimulus sample had 1.81% of sodium chloride and the stimulus samples had 1.80%, 1.35%, 0.90%, 0.45% and 0.0% of sodium chloride. The CAT of 0.84% ​​sodium chloride was calculated, demonstrating that only after reducing 53.59% in the sodium chloride content the sensorial acceptance of cracked is compromised. In addition, it was found that only the cracker without the addition of sodium chloride is sensorially rejected by consumers. The results indicate that it is possible to gradually reduce the sodium content of crackers without occurring in less acceptance by consumers.